2021
DOI: 10.3390/metabo11090564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Variant in APOB Gene as a Major Cause of Hypobetalipoproteinemia in Lebanese Families

Abstract: Familial hypobetalipoproteinemia (FHBL) is a codominant genetic disorder characterized by reduced plasma levels of low-density lipoprotein cholesterol and apolipoprotein B. To our knowledge, no study on FHBL in Lebanon and the Middle East region has been reported. Therefore, we conducted genetic studies in unrelated families and probands of Lebanese origin presenting with FHBL, in order to identify the causes of this disease. We found that 71% of the recruited probands and their affected relatives were heteroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is suggested that this correlation is due to the fact that PCSK9 acts as an important regulator of LDL metabolism through targeting the LDLR for lysosomal degradation, but also due to a direct interaction between PCSK9 and LDL (Abifadel et al, 2010;Tavori et al, 2015). Further studies of PCSK9 levels in patients with hyperchylomicronemia would be interesting in order to verify if all homozygous patients with T1HLP have low PCSK9 levels, or if it is specific to the patients in the studied family, and to decipher the causes of this decrease, as well as the mechanism, the role of PCSK9, and its correlation with ApoB levels (Ayoub et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that this correlation is due to the fact that PCSK9 acts as an important regulator of LDL metabolism through targeting the LDLR for lysosomal degradation, but also due to a direct interaction between PCSK9 and LDL (Abifadel et al, 2010;Tavori et al, 2015). Further studies of PCSK9 levels in patients with hyperchylomicronemia would be interesting in order to verify if all homozygous patients with T1HLP have low PCSK9 levels, or if it is specific to the patients in the studied family, and to decipher the causes of this decrease, as well as the mechanism, the role of PCSK9, and its correlation with ApoB levels (Ayoub et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Disease-associated mutations in APOB are largely composed of truncations, splice variants, and nonsense mutations. Only one missense mutation has been identified, p.Arg463Trp, which was originally reported as “p.Arg490Trp” when first described in 2003 (Hooper et al 2005 ; Ayoub et al 2021 ). This mutation is found primarily in individuals of Lebanese descent (Ayoub et al 2021 ).…”
Section: Enzymes and Metabolismmentioning
confidence: 99%
“…Only one missense mutation has been identified, p.Arg463Trp, which was originally reported as “p.Arg490Trp” when first described in 2003 (Hooper et al 2005 ; Ayoub et al 2021 ). This mutation is found primarily in individuals of Lebanese descent (Ayoub et al 2021 ). The exact mechanism by which it induces HHBL remains unclear.…”
Section: Enzymes and Metabolismmentioning
confidence: 99%